You could make a small (easily repaired) leak and watch it for the amount of time you need to conclude what you need to.
3(5b-1)=5
Get rid of the brackets
15b-3=5
add 3 to both sides of the equation
15b=8
divide both sides of the equation by 15
b=0.53
4(3y-1)=20
12y-4=20
12y=24
y=0.5
Step-by-step explanation:
You are just replacing the 'n' with the number in the 'n box'.
So if this is the formula:
![b(n) = 4 - (n \div 3)](https://tex.z-dn.net/?f=b%28n%29%20%3D%204%20-%20%28n%20%5Cdiv%203%29)
then:
B(-3)= 4-(-3/3)
B(-3)= 4-( -1)
B(-3)= 4+1
B(-3)= 5
B(0)= 4-(0/3)
B(0)= 4-0
B(0)= 4
B(3)= 4-(3/3)
B(3)= 4-1
B(3)= 3
Answer:
$440
Step-by-step explanation:
notes $2 - n
notes $10 - m
n + m = 80 ----------> m = 80 - n
1 - 2/5 = 3/5
![\frac{3}{5} * n = m - 8](https://tex.z-dn.net/?f=%5Cfrac%7B3%7D%7B5%7D%20%2A%20n%20%3D%20m%20-%208)
![\frac{3}{5} * n = 80 - n - 8 \\\\\frac{3}{5} * n + n = 72\\\\\frac{8}{5} * n = 72\\n = 45 \\m = 35\\](https://tex.z-dn.net/?f=%5Cfrac%7B3%7D%7B5%7D%20%2A%20n%20%3D%2080%20-%20n%20-%208%20%5C%5C%5C%5C%5Cfrac%7B3%7D%7B5%7D%20%2A%20n%20%2B%20n%20%3D%2072%5C%5C%5C%5C%5Cfrac%7B8%7D%7B5%7D%20%2A%20n%20%3D%2072%5C%5Cn%20%3D%2045%20%5C%5Cm%20%3D%2035%5C%5C)
45 * $2 + 35 * $10 = 90 + 350 = $440